Exploring self-directed continuous professional development for English Language teachers in selected Namibian secondary schools - Amakutuwa, Hilma Ndesheetelwa Mwalengwa (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
Continuous professional development (CPD) for teachers, with all its diverse notions, has been noted and articulated in various policy documents in Namibia, and is understood as in-service training and professional development for teachers to improve learning outcomes. In Namibia, challenges have been experienced with the performance of learners in English as a Second Language (ESL) at the national level, and teacher professional development could be one way of changing the status quo. However, in answer to the call from the Namibian Ministry of Education Arts and Culture for a more idiosyncratic orientation, limited literature was found on how ESL teachers use self-directed learning (SDL) to shape their CPD activities. Thus, the purpose of this study was to address this gap by exploring the self-directed CPD needs of English Language teachers in selected Namibian secondary schools. The study was oriented to theoretical insights from SDL, reflective practice and social constructivism. Through the use of a qualitative approach, the study employed an exploratory case study research design. Semi-structured interviews and focus group discussions were used to generate data from eight selected Grade 8 to 12 ESL teachers in the Khomas region of Namibia. The data gathered were analysed using an inductive thematic framework. The findings of the study indicate that ESL teachers are faced with a myriad of challenges ranging from classroom experiences, the type of learners they work with and the support system available at school, regional and national level. The study found that due to changing education paradigms, ESL teachers need to broaden their knowledge base in specialised education and systematic professional interventions at school level. They indicated that this would help learners with challenges in reading, writing and comprehension to improve their skills in ESL classrooms. They further emphasised the necessity for mentors, education specialists, systematic schools and circuit based collaborative CPD, as well as more support from school heads and regional ESL senior education officers, which is an area that is inadequately managed. Finally, they pointed out that in order to make their ESL classes engaging and enjoyable, teachers needed to have a strong foundation in ICT education. This foundation can be leveraged to create resources that are now lacking. The findings have implications for ESL teachers, school administrators, education specialists and policymakers, as they provide insights and recommendations for enhancing ESL education practices.
Keywords: English language-- Study and teaching-- Namibia; English teachers-- Namibia; Continuing professional development; Self-managed learning; Reflective practice